Role of complement factor D in cardiovascular and metabolic diseases - Kong, Yingjin; Wang, Naixin; Tong, Zhonghua; Wang, Dongni; Wang, Penghe; Yang, Qiannan; Yan, Xiangyu; Song, Weijun; Jin, Zexi; Zhang, Maomao (Frontiers in Immunology, 2024)
In the genesis and progression of cardiovascular and metabolic diseases (CVMDs), adipose tissue plays a pivotal and dual role. Complement factor D (CFD, also known as adipsin), which is mainly produced by adipocytes, is the rate-limiting enzyme of the alternative pathway. Abnormalities in CFD generation or function lead to aberrant immune responses and energy metabolism. A large number of studies have revealed that CFD is associated with CVMDs. Herein, we will review the current studies on the function and mechanism of CFD in CVMDs such as hypertension, coronary heart disease, ischemia/reperfusion injury, heart failure, arrhythmia, aortic aneurysm, obesity, insulin resistance, and diabetic cardiomyopathy.